96 Adjuvant treatment for adenosarcoma confined to the uterus provides no survival benefit. (13th November 2020) - Nasioudis, D; Latif, N; Ko, E; Haggerty, AF; Cory, L; Morgan, MA; Giuntoli, RL
Abstract : Introduction: Aim of the present study was to investigate patterns of use and outcomes of adjuvant treatment for patients with stage I adenosarcoma. Methods: Patients diagnosed between 2004–2015 with stage I adenosarcoma without a history of another tumor who underwent hysterectomy with lymphadenectomy and had at least one month of follow-up were drawn from the National Cancer Database. Patients who received adjuvant chemotherapy (CT) and/or radiotherapy (RT) defined as treatment within 6 months from surgery were identified. Overall survival (OS) was evaluated after generation of Kaplan-Meier curves and compared with the log-rank test. A Cox model was constructed to control for confounders. Results: Among 735 patients with stage I adenosarcoma, 186 (25.3%) received adjuvant treatment; 61.3% RT only, 26.9% CT only and 11.8% both RT and CT. Rate of adjuvant treatment was 14.1% for patients with stage IA compared to 35.8% and 53.3% for those with stage IB and IC, p<0.001. Age, race, insurance, type of treatment facility and co-morbidities did not impact rate of adjuvant treatment administration, p>0.05. Five year OS rate for patients who did not receive adjuvant treatment was 79.9% compared to 63.4%, 68.8% and 74.1% for those who received RT only, CT only and both CT and RT, p=0.002. After controlling for substage, patient age, insurance status and co-morbidities, administration of adjuvant treatment was not associated with a survival benefit (HR: 1.29, 95% CI: 0.92, 1.58) Conclusions: There is no clear benefit in the use of adjuvant treatment for patients with early stage adenosarcoma.